Backpack Effects on Two-Dimensional Gait Spatiotemporal and Kinematic Parameters - Rizaldy, Nardo; Alvin, Alvin; Lingga, Wirawan; Goeij, Ethan B.W.; Ferryanto, F. (Journal of Mechanical Engineering Science and Technology (JMEST), 2022)
Loads could affect the body gait in various ways. Backpacks, sling bags, suitcases, and even trolleys could hugely affect human gait without us realizing it. The effects of these loads have been scientifically researched in biomechanics and sports science for the past few years. For instance, the comparison of walking with and without a backpack could easily reveal significant differences in body segments, which could be utilized for therapy and medicine development. The aim of this research is to determine the differences of the spatiotemporal kinematic parameters between a conventional human gait and a backpack-loaded gait. Some parameters to be highlighted are stride lengths, stride duration, joint angles, linear and angular segment positions, velocities, and accelerations. The method used for marker data acquisition is based on the 2-dimensional Direct Linear Transformation. The results demonstrate that the backpack increases stride lengths and reduces stride duration, contrast to the expected where backpacks would reduce stride lengths. It was observed that the angle between the bag and the body posterior affects the abdomen relative angle, which directly translates to stride lengths as well. During unloaded walking, increases in pelvic rotation contribute to increases in stride length with increasing walking speed. However, in loaded walking, the back angle is also a factor in determining kinematic parameters.